Factors affecting teachers' professional performance in the Sultanate of Oman / Said Salim Hamed Al-Harthy - Said Salim Hamed, Al-Harthy (2013)
This research tests a path analytical model of five factors affecting teacher professional performance in the Sultanate of Oman. Data of 236 teachers from the second cycle of basic education system in Oman were analyzed using the path analysis approach with AMOS 18.0 software. The procedures included a) preliminary analysis for the normality and the statistics, b) path analysis to test the goodness-of-fit, to estimate the effects (direct, indirect, and total), to build the parsimony model, and to study the moderator effects of groups. The conceptual framework guiding this study was based on the theory of performance (Campbell et al., 1993), theory of reasoned action (Fishbein & Ajzen, 1975), and the history of the theoretical work; related studies. The instruments of this research were scale of teachers' attitudes towards teaching and the Omani teachers' professional performance evaluation instrument. All research and statistical hypotheses were tested at .05 significant level. Findings of the fit tests indicated a good fit indices with the overall sample data (χ2= 3.64, df = 4, p = .457). The path analytical model of factors affecting teachers professional performance has approved that there are only two factors affecting, directly, the teachers performance. They are teachers' work experience (β = .25, p > .05) and the cumulative grade point average (β = .44, p > .05). Whereas, teachers' attitudes towards teaching, in-service training, and teachers' self-professional development are, statistically, non-affecting factors. Also, the path analytical model of factors affecting teachers’ i professional performance has proved that there is only one factor having an indirect effect on the teachers' performance through the work experience. That is the in-service training factor by significant value 0.09 of standardized path coefficient. Findings also show that there are nine total effects among the model variables. The weakest is the total effect of self-professional development on teachers professional performance and the strongest is total effects of teachers’ attitudes towards teaching on self-professional development. Finally, the comparison tests between path models of teachers’ gender and their specialization reveal significant difference between male and female models and between applied and human science teachers' models. Therefore, both gender and specialization of Omanis teachers are considered to be moderators for the relationships between the studied factors of the fitted path model.